Perencanaan Pelayanan Program Stunting - Renny Febrina Arif; Sentot Imam Suprapto; Ratna Wardani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Stunting is a condition of failure to grow in children under five years of age (for infants under the age of five) caused by chronic malnutrition so that children are too short for their age. if not quickly prevented, it will affect the level of children's intelligence and health status in adulthood and emotional development which results in economic losses that may occur in the future, but in certain circumstances and conditions stunting sufferers can also be fatal, which can cause death for the sufferer. This research is a qualitative study with the type of case study research (case study) and is descriptive in nature. This research was conducted at the Sangurara Palu Health Center. With a total of 24 key informants and 5 triangulators as a comparison to ensure the truth of the informant's answer. The data collection technique used in this research is to use interview techniques. The data analysis method used is data collection, data condensation, data presentation, and conclusion drawing. The results of this study are that in planning the stunting program services carried out in the Sangurara Palu Puskesmas work area through several stages, namely starting with setting goals related to reducing the number of stunting, planning socialization activities, fulfilling nutrition for pregnant and lactating mothers, providing exclusive breastfeeding, monitoring child growth and development, maintaining environmental hygiene, controlling stunting patients, visiting patients' homes, immunization, providing basic necessities, and family assistance teams. Then set targets, namely adolescents, prospective couples of childbearing age / prospective brides, pregnant women, breastfeeding mothers, mothers with children under five 0-59 months. Then set the time both the time of day of implementation or related to the length of time needed. And the last is planning the amount of budget needed during the implementation of the activity program.Keywords: Service Planning; Stunting Program; Sangurara Palu Health Center.